Twitch the Corporate Green Tale - An Empirical Study on the Learning Styles to Enhance Green Supply Chain Practices - VenkatesaNarayanan, Padmalalitha Thennal; Thirunavukkarasu, Rajeswari (SDMIMD Journal of Management, 2021)
With an increasing awareness of environmental impacts, corporates are migrating from traditional supply chain operations to green supply chain operations. In this endeavor of corporate greening, employees' roles and functions are transformed to become extensions of learning roles to enhance green practices. The employees, through their job roles, are receptive to learning about green supply chain practices in different ways through different learning styles. Understanding which learning style enhances green supply chain practices in the organization will be beneficial to structure appropriate learning interventions. For this study, 12 manufacturing companies were selected based on convenience sampling. In total, 270 respondents were chosen based on disproportionate stratified random sampling from 12 manufacturing companies through questionnaire. Bayesian Linear Regression was performed on the data collected. This empirical study establishes that employees' learning styles can play a pertinent role in enhancing green practices in organizations. The learning styles drive, support and exploit the full-fledged potential of Green Procurement and Green Manufacturing practices but no significant impact on Green Distribution and Reverse Logistics. The understanding derived from the analysis is depicted as ‘Learn and Act' Cycle of green supply chain practices.